Effect of Sowing Dates and Nitrogen Levels on Population of Okra Jassids (Amrasca biguttula biguttula Ishida) - Regmi, Rajendra; Poudel, Sujata; Regmi, Ram Chandra; Shrestha, Jiban (Indonesian Journal of Agricultural Research, 2020)
Okra (Abelmoschus esculentus L. (Moench) is one of the most important vegetable crops grown in Nepal. The crop is susceptible to various insect pests of which jassids (Amrasca biguttula biguttula Ishida.) is most predominant which reduces production and deteriorates seed quality of okra. A field study was conducted at Horticulture Farm, Agriculture and Forestry University, Rampur, Chitwan, Nepal to elucidate the effect of sowing date and nitrogen levels on the population and damage of jassids from April to September 2018. Three levels of nitrogen (100, 200 and 300 kg N ha-1) and five sowing dates (8th April, 20th April, 2nd May, 14th May and 26th May, 2018) were evaluated in randomized complete block design with three replications. Results indicated that the highest damage score was recorded in okra which was sown on 8th April (2.39) followed by 20th April (2.31) and 2nd May (1.26). The highest damage score of jassids was obtained with the use of nitrogen at the rate of 200 kg ha-1 (1.94) followed by 300 kg/ha (1.72) and 100 kg ha-1 (1.54). Mean population of jassids was maximum with okra sown on 20th April (29.91) and minimum with okra sown on 26th May (6.95). This study showed that late planting i.e. 26th May and applying low level of nitrogen i.e. 100 kg N ha- 1is an effective approach for reducing the jassids population and its damage in okra.